Pharmacokinetics, Pharmacodynamics and Tolerability of Opicapone, a Novel Catechol-O-Methyltransferase Inhibitor, in Healthy Subjects: Prediction of Slow Enzyme–Inhibitor Complex Dissociation of a Short-Living and Very Long-Acting Inhibitor - Almeida, Luis; Rocha, José Francisco; Falcão, Amílcar; Nuno Palma, P.; Loureiro, Ana I.; Pinto, Roberto; Bonifácio, Maria João; Wright, Lyndon C.; Nunes, Teresa; Soares-da-Silva, Patrício (Clinical pharmacokinetics, 2013)
Background and Objectives Opicapone is a novel catechol- O -methyltransferase (COMT) inhibitor. The purpose of this study was to evaluate the tolerability, pharmacokinetics (including the effect of food) and pharmacodynamics (effect on COMT activity) following single oral doses of opicapone in young healthy male volunteers. Methods Single rising oral doses of opicapone (10, 25, 50, 100, 200, 400, 800 and 1,200 mg) were administered to eight groups of eight subjects per group (two subjects randomized to placebo and six subjects to opicapone), under a double-blind, randomized, placebo-controlled design. In an additional group of 12 subjects, a 50 mg single dose of opicapone was administered on two occasions, once having fasted overnight and once with a high-fat high-calorie meal. Results Opicapone was well tolerated at all doses tested. The extent of systemic exposure (area under the plasma concentration–time curve and maximum plasma concentration) to opicapone and metabolites increased in an approximately dose-proportional manner and showed a decrease following concomitant ingestion of a high-fat high-calorie meal. The apparent terminal elimination half-life of opicapone was 0.8–3.2 h. Sulphation appeared to be the main metabolic pathway for opicapone, and both opicapone and the main sulphated metabolite are likely excreted by the biliary route. Maximum COMT inhibition by opicapone was dose dependent, ranged from 36.1 % (10 mg) to 100 % (200 mg and above), and reached statistical significance at all doses tested. The long duration of COMT inhibition by opicapone, however, tended to be independent from the dose taken. The observed half-life of opicapone-induced COMT inhibition in human erythrocytes was 61.6 h (standard deviation [SD] = 37.6 h), which reflects an underlying dissociative process with a kinetic rate constant of 3.1 × 10 −6 s −1 (SD = 1.9 × 10 −6 s −1 ). Such a process compares well to the estimated dissociation rate constant (k off ) of the COMT–opicapone molecular complex (k off = 1.9 × 10 −6 s −1 ). Conclusions Opicapone was well-tolerated and presented dose-proportional kinetics. Opicapone demonstrated marked and sustained inhibition of erythrocyte soluble COMT activity. Based on the observation that the half-life of COMT inhibition is independent of the dose and that it reflects an underlying kinetic process that is consistent with the k off value of the COMT–opicapone complex, we propose that the sustained COMT inhibition, far beyond the observable point of clearance of circulating drug, is due to the long residence time of the reversible complex formed between COMT and opicapone. Globally, these promising results provide a basis for further clinical development of opicapone.